2018
DOI: 10.3233/jad-180234
|View full text |Cite
|
Sign up to set email alerts
|

Minor Hallucinations in Alzheimer’s Disease

Abstract: We have shown that the presence of MHs in patients with newly diagnosed, untreated AD and aMCI is more than controls. MHs were correlated with other behavioral symptoms and a worse cognitive performance. We suggest the specific interrogation for MHs as a clinical feature for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Asking about hallucinations at an early stage makes it possible to have a description of them not by relatives but by the patients themselves. The most frequent symptoms were passage (26.7% of patients) and presence (24.3%) of hallucinations, which is consistent with a previous study on MCI patients [ 32 ]. Globally, 63.5% of the pro-DLB group had hallucinations and 31% had at least two types of hallucinations.…”
Section: Discussionsupporting
confidence: 91%
“…Asking about hallucinations at an early stage makes it possible to have a description of them not by relatives but by the patients themselves. The most frequent symptoms were passage (26.7% of patients) and presence (24.3%) of hallucinations, which is consistent with a previous study on MCI patients [ 32 ]. Globally, 63.5% of the pro-DLB group had hallucinations and 31% had at least two types of hallucinations.…”
Section: Discussionsupporting
confidence: 91%
“…Asking about hallucinations at an early stage makes it possible to have a description of them not by relatives but by the patients themselves. The most frequent symptoms were passage (26.7% of patients) and presence (24.3%) hallucinations, which is consistent with a previous study on MCI patients [32]. Globally, 63.5% of the pro-DLB group had hallucinations and 31% had at least two types of hallucinations.…”
Section: Clinical Issuessupporting
confidence: 90%
“…Concerning minor hallucinations, one study found prevalences of 13% in amnestic MCI and 21% in untreated mild and moderate AD, with higher frequency of presence hallucinations followed by passage hallucinations and visual illusions [63]. Of note, the frequency and severity of psychosis are usually higher for those bearing amyloid pathology [64].…”
Section: Prevalence and Clinical Relevancementioning
confidence: 99%